Penerapan Nilai-nilai Pendidikan Karakter melalui Kegiatan Makan Bersama pada kelas 3 di UPTD SD Negeri 2 Bakam - Putri Nuraini Sugia; M Iqbal Arrosyad; Gatot Afrianto (Universitas Muhammadiyah Bangka Belitung, 2026)
The purpose of this research is to identify the character education values embedded in eating-together activities and their application in the daily lives of children. This study employed a descriptive qualitative approach to examine the implementation of character education values through eating-together activities among third-grade students at UPTD SD Negeri 2 Bakam. Primary data were collected from the principal, teachers, and third-grade students, while secondary data were obtained from books, internet sources, and school documentation. Data were collected through observation, interviews, and documentation, and analyzed by reviewing and interpreting all collected information systematically. The findings indicate that eating-together activities contribute to the development of positive character traits, strengthen solidarity among students, and foster habits of sharing and appreciating food. Furthermore, these activities support the sustainability of character education within the school environment. Therefore, eating together serves not only as a daily routine but also as an effective medium for instilling positive values in students' everyday lives.